The influence of olfactory marketing on clients` loyalty - Marques, S.; Cardoso, M. (Atas XXIV Jornadas Luso Espanholas de Gestão Científica, 2014)
This study refers to marketing and consumer behaviour trying to analyse the relationship between the Olfactory Marketing and consumer loyalty. The research is based on a sample of 390 people, data collected through an online questionnaire. Respondents are customers of chain store Zara Home where Olfactory Marketing is used. The questionnaire was made available on the website of Zara Home Facebook. To answer the questionnaire a prior requirement was considered – the respondent should have made a purchase in this group of stores and had to have visited the store recently. A convenience sample was then collected. The authors conducted an exploratory data analysis and concluded that Olfactory Marketing induces changes in the emotional state of consumers, captures their attention and is a topic of conversation. In conjunction with other factors it can induce more shopping, have a positive impact on satisfaction and loyalty.